2020
DOI: 10.1002/rcs.2068
|View full text |Cite
|
Sign up to set email alerts
|

Totally laparoscopic and totally robotic surgery in patients with left‐sided colonic diverticulitis

Abstract: Background: Introduction of the da Vinci Xi system has facilitated the use of robotics in colorectal surgery. Nevertheless, data on the outcomes of robotic surgery for the treatment of colonic diverticulitis have remained scarce. Methods: Patient demographics, clinical characteristics, and perioperative outcomes of the patients undergoing totally robotic with the da Vinci Xi system or laparoscopic surgery for left-sided colonic diverticulitis (LCD) were compared. Results: Laparoscopic and robotic groups includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
37
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(38 citation statements)
references
References 26 publications
(35 reference statements)
0
37
0
Order By: Relevance
“…In this recent study, Keller et al showed that laparoscopic surgery for colorectal cancer in the elderly, in addition to the clinical benefits, reduces overall costs in comparison to open surgery [ 15 ]. Robotic surgery was born to overcome the limits of laparoscopy (2-D vision, reduced ergonomics in confined spaces, tremor effect and unnatural hand–eye coordination) and was successfully applied to urology, general and pediatric surgery, gynaecology, and other surgical fields [ 11 , 12 , 17 , 28 , 29 ]. Robotic surgery has some advantages, such as shorter learning curve, 3-D views, increased wrist flexibility, better ergonomic benefits, reduction of hand tremor and surgeon workloads [ 8 , 11 , 12 , 16 , 17 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In this recent study, Keller et al showed that laparoscopic surgery for colorectal cancer in the elderly, in addition to the clinical benefits, reduces overall costs in comparison to open surgery [ 15 ]. Robotic surgery was born to overcome the limits of laparoscopy (2-D vision, reduced ergonomics in confined spaces, tremor effect and unnatural hand–eye coordination) and was successfully applied to urology, general and pediatric surgery, gynaecology, and other surgical fields [ 11 , 12 , 17 , 28 , 29 ]. Robotic surgery has some advantages, such as shorter learning curve, 3-D views, increased wrist flexibility, better ergonomic benefits, reduction of hand tremor and surgeon workloads [ 8 , 11 , 12 , 16 , 17 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Robotic surgery was born to overcome the limits of laparoscopy (2-D vision, reduced ergonomics in confined spaces, tremor effect and unnatural hand–eye coordination) and was successfully applied to urology, general and pediatric surgery, gynaecology, and other surgical fields [ 11 , 12 , 17 , 28 , 29 ]. Robotic surgery has some advantages, such as shorter learning curve, 3-D views, increased wrist flexibility, better ergonomic benefits, reduction of hand tremor and surgeon workloads [ 8 , 11 , 12 , 16 , 17 , 30 ]. Comparison between robotic and laparoscopic surgery is considered a “hot topic”.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Further advantages are a tremor and motion filtration, the endowrist function with superior maneuverability of the instrument, three-dimensional binocular vision imaging, and motion scaling. 3 , 4 This explains why resections of para and retro-rectal tumors such as tailgut cysts are particularly suitable operations for robotic surgery.…”
Section: Introductionmentioning
confidence: 99%